Prosedur Perpanjangan Sertifikat Keselamatan Equipment Tb. Mitra Jaya XVI Pada Kantor KSOP Kelas I Dumai oleh PT. Berlian Ocean Shipping Dumai - Wahyu Eka Putri; Syarifur Ridho; Irma Handayani (Jurnal Bisnis Inovatif dan Digital, 2025)
This research aims to provide an in-depth explanation of the extension procedure for the Equipment Safety Certificate of the Tug Boat TB. Mitra Jaya XVI. This process is conducted at the Class I Port Authority and Harbormaster's Office (KSOP) Dumai and managed by PT. Berlian Ocean Shipping Dumai as the shipping agent. The equipment safety certificate is a vital document ensuring the seaworthiness of the vessel's equipment and compliance with maritime regulations. The research methodology utilized is a combination of Field Research—involving direct observation at the site—and Library Research—for gathering relevant regulatory and theoretical data. The findings indicate that the process for managing the certificate extension has generally complied with the established Standard Operating Procedures (SOP). Nevertheless, applicants still face significant obstacles during the application process. These constraints include delays in document inspection by related parties and technical issues within the online SIMKAPEL system (Information Management System for Harbormaster and Ship Services), which frequently experiences disruption. These system outages repeatedly lead to the postponement of certificate issuance. The conclusion of this study emphasizes that while formal procedures are followed, there is a necessity for optimizing the ship agency services and internal supervision. It is crucial to implement improvements to the technical system of SIMKAPEL and enhance internal coordination between surveyors and administrative staff at the KSOP to reduce waiting times, ensuring that certificates are issued promptly for the smooth operation of the vessel.